Planejamento estratégico: planejamento estratégico da coordenadoria de serviços compartilhados – CSC de entidades de ensino, saúde e lazer, educação empresarial e de promoção e defesas de interesses - Barth, Sérgio Ivo (Universidade do Vale do Rio dos Sinos, 2011)
This paper aims at the importance of strategic planning in the management of a coordinating body of corporate services, especially by aligning with the strategic planning of organizations to which it provides corporate services. It starts with the theoretical foundation on strategic planning and implementation, highlighting the strategic map as a tool of planning control, as well as its alignment with the other entities. It is used as research methodology the interviews with managers of the client entities. Compiling the results with the theoretical, it suggests the need for a strategic planning for the corporate services provider, as well as its alignment with its clients. Since the purpose of this department is to get better control of its actions, it looks like the best tool for this is the strategic map, with its goals and indicators, which is an important instrument to support in understanding the full potential of service provider and also in the process of decision making. At the end of the paper it is presented a proposed map with strategic objectives and indicators.
Keywords: Estratégia; Planejamento estratégico; Mapas estratégicos; Strategy; Strategic planning; Strategy maps